An Adaptive Video Streaming Control System: Modeling, Validation, and Performance Evaluation - Luca De Cicco; Saverio Mascolo (IEEE/ACM Transactions on Networking, 2014)
Adaptive video streaming is a relevant advancement with respect to classic progressive download streaming a la YouTube. Among the different approaches, the video stream-switching technique is getting wide acceptance, being adopted by Microsoft, Apple, and popular video streaming services such as Akamai, Netflix, Hulu, Vudu, and Livestream. In this paper, we present a model of the automatic video stream-switching employed by one of these leading video streaming services along with a description of the client-side communication and control protocol. From the control architecture point of view, the automatic adaptation is achieved by means of two interacting control loops having the controllers at the client and the actuators at the server: One loop is the buffer controller, which aims at steering the client playout buffer to a target length by regulating the server sending rate; the other one implements the stream-switching controller and aims at selecting the video level. A detailed validation of the proposed model has been carried out through experimental measurements in an emulated scenario.
Keywords: Performance evaluation; Adaptation models; Adaptive systems; Video on demand; Bandwidth; Switches; Streaming media; Control systems; Servers; Web sites; Adaptive video streaming; modeling; performance evaluation; stream-switching